Qualitative and Quantitative Analysis of Hydroquinone in Face Cream with TLC and HPLC Methods - Dona, Rahma; Selvia, Selvia (Universitas Islam Lamongan, 2020)
Hydroquinone is a chemical compound widely used in cosmetics that acts as a removal of black spots/spots on the face. The use of hydroquinone in cosmetics, according to BPOM regulations, is only allowed with a maximum level of 2%. Excessive use of hydroquinone can cause pigment abnormalities in the face. The materials used in this study were hydroquinone BPFI, 96% ethanol, absolute ethanol, sodium sulfate, methanol (HPLC grade), aquadest, ethyl acetate, and face cream samples (X and Y). Qualitative and quantitative analysis of hydroquinone content in both face cream samples was carried out by TLC and HPLC methods. The results of the qualitative analysis by TLC on both face cream samples (X and Y creams) showed that both samples had the same Rf value 1as the standard hydroquinone Rf while the HPLC chromatogram results of both samples had the same retention time as the standard hydroquinone. Simultaneously, the results of quantitative analysis on cream X samples contained hydroquinone of 3.06% and Y cream of 4.15%. From these results, both face cream samples positive contained hydroquinone with levels> 2%.